Asymmetric dihydroxylation route to (-)-bulgecinine - Show, Krishanu; Upadhyay, Puspesh K.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
The stereoselective synthesis of (-)-bulgecinine is reported from L-aspartic acid using Sharpless asymmetric dihydroxylation and intramolecular cyclization via nucleophilic displacement of alpha-tosylate as key steps. (C) 2011 Elsevier Ltd. All rights reserved.

Stereoselective synthesis of ophiocerins A and C - Show, Krishanu; Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An efficient synthesis of ophiocerins A and C has been achieved via a common intermediate. The stereogenic centers were generated by means of Jacobsen's hydrolytic kinetic resolution and Sharpless kinetic resolution. (C) 2011 Elsevier Ltd. All rights reserved.

Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines

Chemoselective deprotection of N-allylic amines using DDQ - Kumar, Pradeep; Cherian, Shijo K.; Jain, Ruchi; Show, Krishanu (Tetrahedron Letters, 2014)
A highly chemoselective and simple method for the deprotection of N-allylic amines using DDQ has been developed. The use of DDQ in dichloromethane-water provides a mild and efficient one-step deallylation of a wide variety of orthogonally protected tertiary amine derivatives. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chemoselective deprotection; DDQ; N-Allylic amines; Orthogonally protected tertiary amines

Synthesis of ophiocerins A, B and C, botryolide E, decarestrictine O, stagonolide C and 9-epi-stagonolide C employing chiral hexane-1,2,3,5-tetraol derivatives as building blocks - Show, Krishanu; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
An organocatalytic approach to the synthesis of (2R,3S)-hexane-1,2,3,5-tetraol (11) derivatives (in the forms of different stereoisomers and bearing different protecting groups) has been developed. The key chiral intermediates 11 were prepared with complete stereocontrol through the proline-catalyzed intermolecular aldol reaction between acetone and d-glyceraldehyde acetonide. The synthetic utility of the intermediates was demonstrated by their transformation into the title hydroxylated pyrans and a variety of unsaturated lactones through standard synthetic protocols.

First total synthesis of the proposed structure of pandangolide 1 - Show, Krishanu; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2018)
The first total synthesis of the proposed structure of pandangolide 1 is reported. The synthesis was carried out using both an organocatalytic approach and a chiral-pool approach. The required stereochemistry at C-3 and C-5 was installed by using an organocatalytic aldol reaction and a stereoselective ketone reduction. The construction of the 12-membered core was achieved by 2-methyl-6-nitrobenzoic anhydride-mediated Shiina lactonization. The structure of target molecule was confirmed unambiguously by single-crystal X-ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product.
Keywords: lactones; Macrocycles; Natural products; structure elucidation; synthesis design; Total synthesis